Delayed Presentation of Splenic Pseudoaneurysm and its Management: A Case Report - Ahuja, Priya; Goyal, Divakar (Medical Science: Trends and Innovations Vol. 12, 2025)
Background: Splenic pseudoaneurysm following splenic trauma is a rare but serious complication with a high risk of rupture. Percutaneous embolization has emerged as the preferred treatment modality in hemodynamically stable patients. However, the exact timing of pseudoaneurysm appearance and the management of multiple pseudoaneurysms remain unclear and lack standardized protocols. Methods: The study presents a case of a 35-year-old female with a Grade 4 splenic injury (according to the AAST grading system) who did not have any pseudoaneurysm on her initial contrast-enhanced CT. However, on post-injury day 5, ultrasound (USG) revealed multiple splenic pseudoaneurysms, which were further confirmed by CT angiography. The patient underwent percutaneous Gelfoam embolization to manage these various pseudoaneurysms. Results: The patient underwent successful Gelfoam embolization, effectively controlling the multiple pseudoaneurysms in the spleen with no immediate complications. Post-procedural recovery was uneventful, and the patient was discharged after appropriate monitoring. Conclusion: A well-established protocol is necessary to promptly diagnose splenic pseudoaneurysms (PSAs) after solid organ injury. Follow-up imaging, such as USG and CT angiography, should be performed promptly. To reduce interobserver variations, it is recommended that the same radiologist perform the follow-up ultrasound for consistency in the interpretation and detection of complications.